Antagonism within mutualism: host control of symbionts through nodule-specific antimicrobial peptides - Eaker, Ashton A.; Rowe, Shawna L.; Friesen, Maren L. (Frontiers in Microbiology, 2025)
Legumes (Fabaceae) have developed a symbiotic relationship with nitrogen-fixing bacteria called rhizobia to meet their nitrogen needs. Legumes recruit rhizobia from the soil, house them in root organs called nodules, and manipulate bacterial metabolism, providing carbon and receiving bacterially fixed nitrogen in return. One mechanism of host control is through a family of antimicrobial peptides that only appears in the inverted repeat lacking clade (IRLC) of the legumes, though the Dalbergioid clade has similar peptides. They are named nodule-specific cysteine-rich (NCR) peptides due to their exclusive expression in the nodule during symbiosis and the shared 4 or 6 cysteine residue motif. These genes and subsequent proteins vary in number, sequence, and function, but evolutionary genomics research shows that they are adapted from the plant immune system for the new function of symbiont manipulation. In this review, we present the current understanding of NCR peptide biology, expression, and function. We examine NCR genomic and biochemical features and explore their roles in shaping symbiotic outcomes. Finally, we discuss emerging applications and key open questions. Understanding host manipulation of bacterial symbionts within plant tissues provides researchers with targets for engineering more efficient nitrogen-fixing symbioses. In addition, NCR peptides show promise as therapeutic agents with the potential to control both plant and animal pathogens.